Agricultural marketing platforms must demonstrate value to end users - Rutto, Samwel (Technical Centre for Agricultural and Rural Cooperation, 2019)
For online agricultural trading platforms to be scaled and sustained, they need to overcome an array of challenges relating to system design, revenue traction and uptake. Here, Samwel Rutto, regional manager for structured trading systems at the Eastern Africa Grain Council (EAGC), highlights the common pitfalls and key considerations for agribusiness when trying to grow their online client base.